A survey on undergraduates’ multiple intelligences in learning english language at Universiti Malaysia Kelantan - Nooraini Ismail (2021)
This study illustrates the importance of incorporating Multiple Intelligences in learning English language among the Science and Non-Science stream undergraduates. It is believed that this variable could affect their language proficiency. The aims of this study are to identify the preferred types of Multiple Intelligences as perceived by undergraduates and the relationships between the types of Multiple Intelligences and English language grades. The data was collected through an adapted Multiple Intelligences Theory questionnaire that was distributed to 329 undergraduates of Universiti Malaysia Kelantan. 12 of them were also interviewed to identify the way they utilise the Multiple Intelligences in learning English. The finding of this study reveals that regardless of their streams, majority of undergraduates prefer Musical Intelligence in learning English language. Next, the interview data shows the Science stream undergraduates utilised Musical Intelligence and Spatial/Visual Intelligence the most meanwhile the Non-Science undergraduates utilised Spatial/Visual Intelligence the most. Besides, the Spearman’s rho correlation tests demonstrate a statistically significant relationship between Musical Intelligence and English language grades for both streams. The study indicates that learners have their own preferences of Multiple Intelligences in language learning and therefore language instructors should acknowledge the learners’ learning preferences and vary their teaching approaches in order to improve learners’ language proficiency.